Afro Asian colonization: Should European repent for an on going third world underdevelopment - Karim, A.H.M Zehadul (2017)
European colonization in Asia and Africa in the past had fully destroyed the economy and culture of those continents in various ways. It is evidenced that the economic resources of many colonial countries of Asia, Africa as well as Latin America were extracted unscrupulously for the benefit of the Europeans who had simultaneously oppressed the people of these continents to secure their wealth and resources. As a matter of fact, the merciless subjugation of the colonial powers initially began with the destruction of agriculture when the Europeans compelled many of the farmers of these colonial countries to forcibly abandon producing their food crops and instead, compelled them to go for cash crop production. This eventually contributed to the development of a European infrastructure which benefitted and glorified their nations with enormous economic development. While delivering a lecture at Oxford, as recently as in July 2015, Dr. Soshi Tharur, an eminent Indian parliamentarian and a former Minister, raised his voice by blaming specifically the British for colonizing India and extracting its resources which created severe underdevelopment and later having famine there during the Second World War. To corroborate this view, I venture that the British and other colonial powers in Europe during the 16th through 20th century had unrelentingly tortured Asian and African nations causing total destruction of their economic resources. This subjugation is the main cause for the underdevelopment of many of the Third World nations, putting them in real socio-economic crises. Based on the evidence and discussions, the paper finally concludes by posing a question as to whether these colonial nations should repent for their misdeeds in the past and also promise to provide some form of compensation to these colonial nations.